The impact of cultural factors to career readiness in final year undergraduate students - Rahmi Dwi Febriani (Journal of Counseling, Education and Society, 2023)
One of the developmental tasks of students is to choose and prepare for a career carefully. Career readiness is a fundamental component of career transition. Based on the fact  in the field, there are still students who have not prepared their careers well. The data also shows that graduates who have just graduated from college tend to have not considered their abilities, interests, and personality in choosing a job. One of the factors that influence it is culture. Career choices that are only thick with cultural influences will cause career problems. The purpose of this study was to describe the influence of culture on student career readiness. This study uses a literature review approach. The research tries to examine a number of references in the form of books, scientific articles and other documents that discuss students' career readiness.